2019
DOI: 10.1193/012418eqs024m
|View full text |Cite
|
Sign up to set email alerts
|

On the Seismic Fragility Assessment of Concrete Gravity Dams in Eastern Canada

Abstract: In recent years, probabilistic methods, such as fragility analysis, have emerged as reliable tools for the seismic assessment of dam-type structures. These methods require the selection of a representative suite of ground motion records, resulting in the need for a ground motion selection method that includes all the relevant ground motion parameters in the fragility analysis of this type of structure. This article presents the development of up-to-date fragility curves for the sliding limit states of gravity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The records were selected from the PEER NGA-West2 database (Ancheta et al 2013) due to the limited availability of strong ground motion records in the PEER NGA-East database (Goulet et al 2014). Further details on the PSHA and the record selection procedure can be found in Segura et al (2018).…”
Section: Seismic Hazard and Ground Motion Selection Methodsmentioning
confidence: 99%
“…The records were selected from the PEER NGA-West2 database (Ancheta et al 2013) due to the limited availability of strong ground motion records in the PEER NGA-East database (Goulet et al 2014). Further details on the PSHA and the record selection procedure can be found in Segura et al (2018).…”
Section: Seismic Hazard and Ground Motion Selection Methodsmentioning
confidence: 99%
“…In the context of this study, Latin Hypercube sampling (LHS) is adopted to generate the training dataset representing the different configurations of the system under study. This sampling technique was selected because of its ability to divide the desired range of values for each of the m parameters into n equiprobable intervals and then select a sample once from each interval to ensure that the set of samples reflects the entire range of the parameters [29].…”
Section: Experimental Design Matrixmentioning
confidence: 99%
“…The response of each sample was analysed for several levels of seismic intensity through an incremental dynamic analysis (IDA). Most of the studies found in the literature concerning seismic fragility assessment for gravity-dam-type structures use the peak ground acceleration (PGA) or the spectral acceleration at fundamental period of the structure as the seismic intensity measure [10,14,15]. Nevertheless, given that the fundamental period depends on the concrete and foundation modulus of elasticity, defined herein as random variables, the spectral acceleration at the fundamental period varies according to the sample considered for the analysis.…”
Section: Levels Of Seismic Intensitymentioning
confidence: 99%
“…The most recent studies were from Bernier et al [10,11], Hariri-Ardebili and Saouma [12], Lallemant et al [13] and Segura et al [14]. In the first two studies [10,11], the finite element method is used to model a single block of a case study dam considering DRF interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation